Web-based Project Tracking and Critical Path Evaluating System - Sroidokson, Nanida (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
The contral objective of this study was to study users’ problems and requirements, develop, and study the satisfaction of users toward Web-based Project Tracking and Critical Path Evaluating System. The data were collected from 4 specialists in the area of project management and software development. Most of them could not achieve as planned due to lack of tracking tool. Therefore, Critical Path Method was applied to Web-based Project Tracking and Critical Path Evaluating System at planning stage for setting up timeframe of the project. The experimental stage was tested by 10 other specialists by using interviews and satisfactory surveys. The satisfaction of users was evaluated by averages () and standard deviation (S.D.) of scores including the in-depth interviews of users. The research findings showed that the satisfaction of user toward the system on Function Requirement Test was (= 4.22, S.D. = 0.85), Function Test was (= 4.25, S.D. = 0.84), Usability Test was (= 4.38, S.D. = 0.76) and Security Test (= 4.37, S.D. = 0.88), all of which were at very satisfied. The result showed that the system was able to respond to the needs of users and to meet the requirements of the study.